(untitled) (Marketing Journal, 2025)
This article examines the theoretical and practical aspects of inventory management in retail enterprises. The study evaluates the impact of effective inventory control on economic efficiency, explores the use of modern technologies, and presents a compara tive analysis of traditional and innovative methods. The findings provide valuable practical insights for improving inventory management strategies in retail businesses.